IMPLEMENTASI PENGELOLAAN ALOKASI DANA DESA (ADD) DI KAMPUNG LINGGANG MAPAN KECAMATAN LINGGANG BIGUNG KABUPATEN KUTAI BARAT - Nova Sintia Dewi Sitorus; Anthonius Margono; Bambang Irawan (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The purpose of this study is to describe and analyze the Village Fund Allocation Management Implementation (ADD) In Kampung Linggang Steady District of Linggang Bigung West Kutai. As well as to describe and analyze the factors affecting the Village Fund Allocation Management Implementation (ADD) In Kampung Linggang Steady District of Linggang Bigung West Kutai. The study concluded that the ADK Policy Implementation in the village Linggang Mapan not run optimally. It can be seen from the lack of understanding ADK management team in planning the implementation of ADK fund management activities, because the planning process is only done by her team manager ADK without involving all villagers participated.